2010
DOI: 10.1097/ccm.0b013e3181b78671
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aortic balloon counterpulsation in patients with acute myocardial infarction complicated by cardiogenic shock: The prospective, randomized IABP SHOCK Trial for attenuation of multiorgan dysfunction syndrome*

Abstract: In this randomized trial addressing addition of IABP in CS patients, mechanical support was associated only with modest effects on reduction of APACHE II score as a marker of severity of disease, improvement of cardiac index, reduction of inflammatory state, or reduction of BNP biomarker status compared with medical therapy alone. However, the limitations of our present trial preclude any definitive conclusion, but request for a larger prospective, randomized, multicentered trial with mortality as primary end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
158
3
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(184 citation statements)
references
References 36 publications
3
158
3
12
Order By: Relevance
“…In contrast to our results, the original pa per of Elebute and Stoner showed a sig nificant distinction between survivors and nonsurvivors at a cutoff of 20 points for [33]. The APACHE II/III or SAPS II scores were recorded on the day of CS diagnosis and at their maximum value; it is, however, possible that some of the nonsurvivors developed sepsis and MODS after diagnosis and therefore led to increased scores in the course of the ill ness.…”
Section: Scoring In Cardiogenic Shockcontrasting
confidence: 53%
See 2 more Smart Citations
“…In contrast to our results, the original pa per of Elebute and Stoner showed a sig nificant distinction between survivors and nonsurvivors at a cutoff of 20 points for [33]. The APACHE II/III or SAPS II scores were recorded on the day of CS diagnosis and at their maximum value; it is, however, possible that some of the nonsurvivors developed sepsis and MODS after diagnosis and therefore led to increased scores in the course of the ill ness.…”
Section: Scoring In Cardiogenic Shockcontrasting
confidence: 53%
“…Intraaortic balloon pump (IABP) is a commonly used mechanical support sys tem for patients with CS [25,33]. Despite intensive therapy, these patients often de velop a systemic inflammatory response syndrome (SIRS) progressing to multiple organ dysfunction syndrome (MODS) and subsequent death due to multiple or gan failure [6,39].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(nitric oxide synthase inhibitors), which lowered mortality [3,4]. With the development of new, perhaps more potent, mechanical cardiac assist devices, the role of IABP therapy in the management of CS in recent studies has again been of major interest [5][6][7][8][9]. Routine use of IABP therapy in the setting of high-risk STEMI is not supported by evidence from randomised trials, as shown in our recently published meta-analysis [10].…”
Section: Introductionmentioning
confidence: 99%
“…43 This was followed with a larger trial of 600 patients with acute MI complicated by cardiogenic shock and randomised patients to either IABP or standard therapy (IABP-SHOCK II), which did not demonstrate a significant reduction in mortality rate at 30 days or 12 months (although 86.6 % of IABPs were inserted post-PCI). 44 Current ESC guidelines advise against the routine use of IABP during PCI in patients with cardiogenic shock, and limit their recommendations of its use to patients with cardiogenic shock due mechanical complications of MI who are awaiting surgery.…”
Section: Intra-aortic Balloon Pumpmentioning
confidence: 99%